2019
DOI: 10.1186/s12887-019-1513-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and seasonal variations of different Enteropathogens in Lebanese hospitalized children with acute gastroenteritis

Abstract: Background Acute gastroenteritis (AGE) is a major cause of pediatric morbidity and mortality around the world. It remains a frequent reason for infection-related admissions to emergency units among all age groups. Following the Syrian refugee crisis and insufficient clean water in our region, we sought to assess the etiological and epidemiological factors pertaining to AGE in South Lebanon. Methods In this multi-center cross sectional clinical study, we analyzed the dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 32 publications
8
28
0
Order By: Relevance
“…In accordance, Shim et al [ 27 ] reported that bacterial gastroenteritis is associated with more episodes of diarrhea and longer-lasting diarrhea than common viral infections. Consequently, our data resulted in a higher VSS score for Campylobacter -positive patients, showing a severe profile of acute gastroenteritis compared to a moderate profile for Campylobacter -negative patients, which is consistent with our previous results on rotavirus and adenovirus cases showing a lower severity of acute gastroenteritis in children when compared to other enteropathogens [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance, Shim et al [ 27 ] reported that bacterial gastroenteritis is associated with more episodes of diarrhea and longer-lasting diarrhea than common viral infections. Consequently, our data resulted in a higher VSS score for Campylobacter -positive patients, showing a severe profile of acute gastroenteritis compared to a moderate profile for Campylobacter -negative patients, which is consistent with our previous results on rotavirus and adenovirus cases showing a lower severity of acute gastroenteritis in children when compared to other enteropathogens [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…Acute gastroenteritis is the second major cause of pediatric morbidity and mortality following acute lower respiratory tract infections in Lebanon and other developing countries [ 17 ]. Identifying specific enteropathogens responsible for acute gastroenteritis is essential for the application of appropriate and suitable clinical measures to manage the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those, 135 (43.8%) were females and 173 (56.2%) were males. Patients were divided into seven age groups between 1 month and 12 years (1-3, 4-11, 12-23, 24-35, 36-47, 48-59 and !60) as previously described [1,19]. The mean family size of patients was 4.21; 61.3% of patients were breastfed; and 35.6% of patients have been previously vaccinated with rotavirus vaccine (Table 1).…”
Section: Socio-demographic and Clinical Characteristics Of Patientsmentioning
confidence: 91%
“…Acute gastroenteritis is one of the most common infectious diseases facing all age groups worldwide, especially the pediatric population [1]. It represents a major health problem particularly in developing countries.…”
Section: Introductionmentioning
confidence: 99%